Clinical Features of Psoriatic Arthritis in Korea - Song, Yeong W.; Choi, Hyo Jin; Youn, Jai Il (Current Rheumatology Reviews, 2008)
This study was undertaken to assess the prevalence of psoriatic arthritis (PsA) in Korean psoriasis patients and to evaluate its clinical features. The authors evaluated 504 patients with psoriasis who visited the dermatology clinic at Seoul National University Hospital. Fifty-three of these patients (10.5%) were diagnosed as having PsA. Plaque-type psoriasis was the most common in both the PsA and psoriasis only groups, and pustular psoriasis was more frequent in the PsA group (19.0%) than in the psoriasis only group (4.3%, p=0.001). Nail change was more common in the PsA group (54.3% vs 35.3%, respectively; p=0.015). Dactylitis and enthesopathy were observed in 8.5% and 9.1% of PsA patients, respectively. Psoriasis was followed by arthritis in 73.6% of PsA patients, with a mean interval of 12.2 ± 10.1 (mean ± SD) years, and spondylitis (43.4%) was the most predominant disease type. HLA-B27 was detected in 21.1% of patients in the PsA group. In conclusion, plaque-type psoriasis was most common in PsA patients, and nail change was more common in PsA patients than in patients with psoriasis only. Spondylitis was the most predominant form of arthritis.
Keywords: enthesopathy